224k views
0 votes
Please help really fast!!!

Please help really fast!!!-example-1
User MattK
by
5.5k points

2 Answers

4 votes

Answer:

The answer is


√(65)

Explanation:

We need to find the distance as instructed.

Its formula is:


d = \sqrt{(x_2 - x_1) ^(2) + (y_2 - y_1)^(2) }

Let's plug in according to the formula and solve.


d = \sqrt{(x_2 - x_1) ^(2) + (y_2 - y_1)^(2) } \\ d = \sqrt{( - 7 - 1) ^(2) + (2 - 3)^(2) } \\ d = √(64 + 1) \\ d = √(65)

User Sayaka
by
5.8k points
2 votes
the answer for this question is 65
User Nahn
by
6.0k points